1998
DOI: 10.2169/internalmedicine.37.804
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Human T-Cell Responses by Altered Peptide Ligands: A New Approach to Antigen-specific Modification.

Abstract: HumanCD4+T-cells recognize antigenic peptides in the context of humanleukocyte antigen (HLA) class II molecules and produce various lymphokines to proliferate and activate other cells. It was once considered that the T-cell response is an all or nothing type event, but recent studies have clearly indicated that T-cells show manydifferent types of activation in recognition of altered ligands for T-cell receptors (TCR). In this review, wesummarizeour recent findings on the human CD4+T-cell response to altered pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…However, in other persistent pathogen infection models, anergy induced by altered peptide ligand antagonism (41)(42)(43), or by T regulatory cells producing either TGF-␀1 or IL-10 (37, 44 -49), has been shown to play a role in down-regulating T cell responses. Although antigenically variant MSP2 epitopes could potentially act as antagonistic peptides, previous studies did not show the ability of naturally occurring variant epitopes to cause anergy of MSP2-specific T cell lines or clones specific for the agonistic MSP2 variant (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, in other persistent pathogen infection models, anergy induced by altered peptide ligand antagonism (41)(42)(43), or by T regulatory cells producing either TGF-␀1 or IL-10 (37, 44 -49), has been shown to play a role in down-regulating T cell responses. Although antigenically variant MSP2 epitopes could potentially act as antagonistic peptides, previous studies did not show the ability of naturally occurring variant epitopes to cause anergy of MSP2-specific T cell lines or clones specific for the agonistic MSP2 variant (10).…”
Section: Discussionmentioning
confidence: 99%
“…Yokomizo and colleagues (34) showed previously that human CD4 Ï© helper T cell clones responded to altered peptides, in which a single residue was altered, following the secretion of different cytokines. Another study showed that two peptides that were otherwise identical apart from a single amino acid induced different types of T cells; one was T helper 1, while the other was T helper 2 (35). Thus, it seems that even a single amino acid difference is critical for T cell recognition and reaction.…”
Section: T Cell Epitope In Type 1 Diabetesmentioning
confidence: 99%
“…This seeming paradox could be explained by the observation that T cells interact with antigen-presenting cells for a prolonged time and that a single specific peptide-HLA complex may serially trigger up to a few hundred TCRs (39). (ii) Evidence has accumulated that the TCR is not just an on-off switch but may be able to transmit qualitatively distinct signals into T cells (15,26,27,34). Minor modifications within the amino acid sequence of a specific peptide can lead to inactive peptides, weaker or stronger agonists and antagonists (32), or so-called altered peptide ligands (APL) (11).…”
Section: Virus-specific Cd4mentioning
confidence: 99%
“…While APL selectively induce certain but not all effector functions or even T-cell anergy (36,37), antagonistic peptides do not activate specific T cells but inhibit stimulation by the wild-type peptide (32). Although different patterns of phosphorylation of TCR subunits have been described after stimulation with APL, the molecular basis for this distinct TCR signaling is still incompletely understood (16,21,26,27,32). (iii) A high affinity between peptide and major histocompatibility complex (MHC) or a high antigen dose may promote the differentiation of naive CD4 Ï© T cells into Th1 cells, whereas a low affinity between MHC and peptide or a low antigen concentration favors the development of a Th2 cytokine profile (4).…”
Section: Virus-specific Cd4mentioning
confidence: 99%